Prognostic value of the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in laryngeal cancer: What should we expect from a meta-analysis? - Hu, Xianyang; Tian, Tengfei; Sun, Qin; Jiang, Wenxiu (Frontiers in Oncology, 2022)
Background: Although many studies have shown the predictive value of the high neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) for various cancers, there are conflicting reports regarding their role in laryngeal cancer. This study aimed to evaluate the relationship between high NLR/PLR and laryngeal cancer prognosis with the help of meta-analysis. Methods: PubMed, Embase and other databases were used to search relevant studies. The pooled hazard ratio (HR) and 95% confidence interval (CI) were calculated using either the random-effect-model or fixed-effect model. Sensitivity analyses and subgroups were used to explore potential sources of heterogeneity. Publication bias was also adopted. Result: 5716 patients from 20 studies were involved in this meta-analysis. Pooled observed survival (OS) (HR=1.70, 95%CI, 1.41-2.04, p=0.00), progression-free survival (PFS) (HR=1.81, 95%CI, 1.47-2.23, p=0.00), and disease-free survival (DFS) (HR=1.86, 95%CI, 1.45-2.38, p=0.00) showed the prediction of high NLR for poor prognosis. It also suggested that high PLR predicted poor OS (HR=1.89, 95%CI, 1.21-2.94, p=0.00). Conclusion: This study indicated that high NLR was associated with poor OS, PFS, and DFS in laryngeal cancer patients, and high PLR was related to poor OS. Both could be potential predictors of prognosis.